The figure of the mother in the English poetry by Rose Auslander - Vikyrchak Iryna Oleksandrivna (Studia Humanitatis, 2016)
The article describes the English poetry of a well-known German-language poet Rose Auslander. Through the example of three poems from the English-language book “The Forbidden Tree” the article analyses the figure of the mother. The English poetry belongs to the third period of Auslander's writing; it was also post-traumatic period in her life: experiences of Chernivtsi ghetto and the death of her mother left a deep scar in the soul of the poetess and caused the change of the language in the poet’s creativity. The search of the contact with her mother through the poetry – despair, hope for the reunion with her native German language, and with Bukovina are the main motifs accompanying the figure of the mother in Auslander's poetry of this period.